Aumento de sólidos totais na dieta líquida de bezerros leiteiros - Rafael Alves de Azevedo (2016)
Although studies clearly point advantages for increasing the volume of milk provided to calves, many dairy farmers are reluctant to adopt this nutritional strategy due to the reduced volume of milk to be sold. One strategy that could partly work around this problem would be the addition of milk replacer in a fixed volume of liquid diet, increasing the total solids (TS) content of the diet provided. This research was carried out to determine the effects of this alternative on the osmolality of the final product, intake, performance and health of calves during pre and postweaning, as well as the rate of passage, apparent digestibility of nutrients, rumen and other organ development, and body composition of dairy calves. Crossbreed Holstein-Gir heifers (n = 60) and crossbred Holstein-Gir calves (n = 32) were randomly assigned to 4 treatments, maintaining a balance regarding body weight at birth, total serum protein concentration and genetic composition. Milk replacer was added to whole milk to adjust TS at 12.5; 15.0; 17.5 and 20.0%. All animals received 6 L/d of liquid diet, divided in two equal meals (0800 and 1600 h), supplied in buckets from 5 to 55 d of age. For heifers, between 56 and 59 days of age, the quantity was reduced by half (0800h) and at 60 d of age they were weaned, being monitored until 90 d of age. The calves were weaned at 56 d of age. Starter and water were provided ad libitum. At 70 d of age, corn silage was included in heifers diet. Intake and health of all animals were evaluated daily whilst body performance and development parameters were performed weekly. From 14 d of age, the ruminal pH was measured in heifers. The rate of passage through the gastrointestinal tract was evaluated using chromium oxide as external marker in calves at 43 d of age; between 50 and 55 d of age, it was performed an evaluation of apparent digestibility of nutrients and at 56 d of age the calves were euthanized for further evaluation of the organs and carcass composition. Fragments of rumen, omasum and intestines were collected for histological evaluation, and samples of ruminal contents and cecum were collected for pH and VFA measurements. After analyzing the treatments, the TS levels of 13.5; 16.1; 18.2 and 20.4% were verified. The osmolality ranged from 264.9 to 533.5 mOsm/L. The heifers showed similar intake regardless (kg/d) of treatment from the fourth week. During the preweaning period, the starter intake was similar and there was a linear increased in water intake with the increase in TS%. The ruminal pH during the preweaning period was similar between the treatments (6.2) as well as the days of diarrhea. The increase in TS% linearly increased body development and performance measures, but linearly reduced feed efficiency. During the postweaning, the starter and water intake, corn silage and total dry matter were similar between treatments, as well as performance and feed efficiency. However, the body development measurements showed a linear increased according to the increase in TS%. These data show that the TS concentrations evaluated were not able to reach the peak of influence of TS intake under heifers performance, suggesting that new strategies with the provision of higher TS% should be evaluated to achieve greater performance during preweaning. In calves, it was observed that the increase in TS% did not alter the rate of passage and nutrient digestibility, as well as the development parameters of the pre-stomachs, intestine and calves' body composition.